Relative Extensions of Modules and Homology Groups - Mao, Lixin; Zhu, Haiyan (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We introduce the concepts of relative (co)extensions of modules and explore the relationship between the relative (co)extensions of modules and relative (co)homology groups. Some applications are given.